Evaluación interactiva en la asignatura de estudios sociales para el séptimo año de educación básica, año 2014 - Chugchilán Tipán, Janeth Paulina (2015)
This research intends to solve a current problem exists in the school of La Maná canton, is characterized by the lack of a system of interactive evaluation, for each reason the teachers choose traditional alternatives for evaluate the learning, in response, a target is set up a system of interactive evaluation system for teachers in the area of social studies in the seventh year of basic education into an interactive CD, which one augmented, realize and check thought a socialization study, that permit check the feasibility and support that the proposal generates positive results of high significance in the assessment of learning.